THE INFLUENCE OF ELECTORAL SYSTEMS ON THE ELECTIONS IN ALBANIA - Berhani, Ilir (European Scientific Journal, ESJ, 2012)
The purpose of the research.The paper wants to answer a current problem and very important to come before the Albanian politics and society, the problem of changing the electoral law and electoral system in Albania. Two recent elections in our country, general elections of 2009 and 2011 local elections were marred by numerous irregularities which have influenced the outcome of the election and brought numerous disputes strong opposition. Political parties, the Albanian society and international community are in discussion adjustments should be made to election legislation that elections are fair, credible and acceptable by both parties. In Albania, all elections are influenced by the election legislation. But have influenced the conduct of elections and election results election systems. Therefore the object of work is mainly the influence of electoral systems on the elections in Albania Methods. Evidence of the election legislation in Albania and its comparison with European and international legislation in this field. Analysis of the election and election results in Albania in the period 1991-2011.Evidencing the influence of electoral systems on election and election results, comparing the results in all elections. Results. From the search derived these results: election systems and distribution formulas of seats have influenced and defined the party in the election outcome; political parties have made adjustments and changes constantly in election systems, passing by a majority system based on absolute majority, combined electoral systems up in regional proportional electoral system. The 2009 elections showed that the regional proportional system had not sustainable governance, and real representation of parties in parliament. Conclusions. The main conclusion. For Albania was wrong application of the regional proportional electoral system. More convenient for Albania is the majoritarian system corrected. Electoral formula of distribution of additional seats bring the number of seats to the number of votes each party receives nationwide. Voter to have available only one ballot and one vote only, that belongs candidate single-member zone and the party the candidate represents. In this way the votes that the voter will cast is a sincere vote.